Energy-Related Adaptations in Low-Income Nonmetropolitan Wisconsin Counties - Tienda, Marta; Aborampah, Osei-Mensah (Journal of Consumer Research, 1981)
Multiple classification analysis is used to examine the relative importance of physical/structural, socioeconomic, and demographic factors in shaping household responses to changes in the cost and availability of energy. Two coping strategies analyzed are switching to alternative and less-expensive fuels for space heating and investing in home retrofitting. Results show that physical/structural characteristics of the familial microenvironments are more important than socioeconomic and family factors in molding consumption levels and behavioral adaptations.